Isolation and identification of cellulolytic bacteria at fibric, hemic and sapric peat in Teluk Bakung Peatland, Kubu Raya District, Indonesia: - - Siti Khotimah; Suharjono Suharjono; Tri Ardyati; Yulia Nuraini (Society for Indonesian Biodiversity, 2020)
Abstract. Khotimah S, Suharjono, Ardyati T, Nurani Y. 2020. Isolation and identification of cellulolytic bacteria at fibric, hemic, and sapric peat in Teluk Bakung Peatland, Kubu Raya District, Indonesia. Biodiversitas 21: 2103-2112. Cellulose degrading bacteria was one of the microbial removers of organic matter contained in the soil into simpler monomers so that it can be utilized by other organisms. The objective of the research was to obtain cellulose-degrading bacteria found on fibric, hemic, and sapric peat in forest and shrubs (oil palm). The bacteria were isolated by pour plate method on 1% CMC media. Selected isolates were assayed quantitatively based on the activity of cellulase enzyme, identified with 16S rDNA. The density of cellulolytic bacteria in the secondary forest peat of fibric, hemic, sapric were 2.1x103 cfu/g, 5.9x104 cfu/g, and 4.9x104 cfu/g whereas, in the area of shrubs/oil palm peat fibric, hemic and sapric 6.9x104 cfu/g, 8.4x104 cfu/g and 3.4x105 cfu/g respectively. There were 19 bacterial isolates that have clear zones around the colony as degradation of cellulose had highest ability to degrade cellulose with clear zones of 5-7 mm. The strain of SB1.1.1 showed highest activity of cellulase enzyme 11.17 U/mL, followed by HH3.1.1 strain and SB2.3 7.83 U/mL. Based on the phylogeny tree, strain SB1.1.1 and HH3.1.1 have the closest kinship relationship with Bacillus cereus with a kinship relationship of 100%, while SB2.3 has the closest kinship relationship with Bacillus stratosphericus with a relationship of 99.85 %.